Research on Photolithography Technology and Photoresist Materials in Chip Manufacturing - Huang, Rui (Transactions on Computer Science and Intelligent Systems Research, 2025)
As semiconductor manufacturing technology evolves, lithography, a core process, faces the dual challenges of achieving higher resolution and smaller feature sizes. This paper explores the fundamental principles and development history of lithography technology, as well as its bottlenecks. It also delves into the differences between conventional organic and novel inorganic photoresists, with a particular emphasis on the unique advantages and reaction mechanisms of novel inorganic photoresists in Extreme Ultraviolet (EUV) lithography. Furthermore, it systematically investigates the photochemical reaction mechanisms of photoresists in EUV and Deep Ultraviolet (DUV) lithography, including processes such as light absorption, photoionization, molecular dissociation, and fragment release. The effects of key factors like photoresist composition, structure, exposure dose, power, and photoresist thickness on the reaction characteristics are thoroughly examined. In addition, it proposes optimization directions for photoresist performance and experimental validation methods, aiming to promote the development of semiconductor manufacturing technology towards higher precision and eco-friendliness.